The 'New Approach' to Public Sector Reforms in Ghana: A Case of Politics as Usual or a Genuine Attempt at Reform?. (2nd February 2016) - Ohemeng, Frank L. K.; Ayee, Joseph R. A.
Abstract : Public sector reforms continue to preoccupy governments all over the world, compelled by the need to 'get the state right' through better policy development and implementation. Developing countries see this as the path to a developmental state. This article examines Ghana's quest to build such a state through its new public sector reforms, originally hailed in hyperbolic terms. We argue that the rejection of a top‐down and bottom‐up synergy in favour of an exclusively top‐down approach dooms this effort to failure.